Docosahexaenoic Acid Suppresses Silica-Induced Inflammasome Activation and IL-1 Cytokine Release by Interfering With Priming Signal - Wierenga, Kathryn A.; Wee, Josephine; Gilley, Kristen N.; Rajasinghe, Lichchavi D.; Bates, Melissa A.; Gavrilin, Mikhail A.; Holian, Andrij; Pestka, James J. (Frontiers in Immunology, 2019)
Occupational exposure to respirable crystalline silica (cSiO2) has been etiologically linked to human au-toimmunity. Intranasal instillation with cSiO2 triggers profuse inflammation in the lung and onset of au-toimmunity in lupus-prone mice; however, dietary supplementation with the omega-3 polyunsaturated fatty acid docosahexaenoic acid (DHA) abrogates these responses. Inflammasome activation, IL-1 cy-tokine release, and death in alveolar macrophages following cSiO2 exposure are early and critical events that likely contribute to triggering premature autoimmune pathogenesis by this particle. Here we tested the hypothesis that DHA suppresses cSiO2-induced NRLP3 inflammasome activation, IL-1 cytokine re-lease, and cell death in the macrophage. The model used was the murine macrophage RAW 264.7 cell line stably transfected with the inflammasome adapter protein ASC (RAW-ASC). Following priming with LPS, both the canonical activator nigericin and cSiO2 elicited robust inflammasome activation in RAW-ASC cells, as reflected by IL-1β release and caspase-1 activation. These responses were greatly diminished or absent in wild-type RAW cells. In contrast to IL-1β, cSiO2 induced IL-1α release in both RAW-ASC and to a lesser extent in RAW-WT cells after LPS priming. Preincubating RAW-ASC cells with 10 and 25 µM DHA for 24 h enriched this fatty acid in the phospholipids by 15- and 25-fold, re-spectively, at the expense of oleic acid. DHA preincubation suppressed both nigericin- and cSiO2-induced inflammasome activation and release of IL-1β and IL-1α. DHA’s suppressive effects were linked to inhibition of transcription of the NF-κB-driven genes Nrlp3, Il1b, and Il1a. Nigericin-induced death was inflammasome-dependent, indicative of pyroptosis, and could be inhibited by DHA pre-treatment. In contrast, cSiO2-induced death was inflammasome-independent, suggestive of necrosis, and not inhibited by DHA. Taken together, these findings indicate that DHA suppresses cSiO2-induced in-flammasome activation and IL-1 cytokine release in macrophages, but was not protective against cSiO2-induced cell death.